Understanding Google Analytics : from beginner to advanced in one day. (O'Reilly Media, Inc., 2018)
Your organization's website is a much more important asset now than it was not that long ago. And the degree to which online commerce is continuing to grow means that you need to be sure your business is getting the most out of its web presence, attracting and maintaining customers, so knowing exactly how your website is performing is essential. Google Analytics is the most popular web analytics tool in use today, and knowing how it works, what it does, and how to extract and share the valuable information it can generate about your web assets is a key skill for any digital marketer to acquire. Understanding how to use Google Analytics effectively will help your career and company to succeed. In this video course, your host, author and award-winning marketer, Eric Enge teaches you everything you need to take advantage of the power of Google Analytics to help your business glean key business insights and act upon them. You'll see how to set up reports and dashboards to communicate critical information to other members of your organization. You'll also learn how to use analytics to find problems and opportunities, apply advanced filtering and segmentation, and more. With these new skills, you will know how to set up a marketing campaign, measure your results, and analyze your customer's behavior. If you're involved in a digital marketing role for your enterprise, this video course will guide you through the basics to some of the advanced aspects of the program and provide enough information for you to pass the Google Analytics Certification Exam. What you'll learn--and how you can apply it How to set up, manage, and use analytics to fine tune your web assets and significantly increase your value to your organization Create reports such as acquisition, behavior, and conversion, as well as dashboards to monitor and share your website's performance with others Understand and set up SEO testing How to apply filters to hone in on metrics that are critical to your business Learn how to use Google Analytics to extract key business insights that can help your business grow Everything you need to pass the Google Analytics Certification Exam This video course is for you because... You're involved in the marketing or technology for the website for your business You want to know how to gain greater visibility into your site's performance, and how to get more out of it You recognize that expertise in Google Analytics can enhance your career with highly sought-after analytics skills Prerequisites: You should have a basic knowledge of your company's website, and how your company uses it to accomplish its business objectives You should possess a desire to understand how to fine tune your website for your business Materials or downloads needed in advance: Although not absolutely required, access to a Google Analytics account will help reinforce the lessons taught in this video course Related Safari materials Read Chapter 1, "Overview," from Introduction to Google Analytics: A Guide for Absolute Beginners Read Chapter 2, "Google Analytics Reporting Overview: User Characteristics and Behavior," from Google Analytics Breakthrough Read Chapter 1, "Ride the Lightning with AMP," from AMP: Building Accelerated Mobile Pages Related materials from around the web Read "About Google Analytics Certification" from Google Read "The Canonical Guide to AMP" from Stone Temple.